Research in the social scientific study of religion. - Piedmont, Ralph L., 1958-; Village, Andrew. (Research in the Social Scientific Study of Religion, 2010)
Research in the Social Scientific Study of Religion publishes empirical and theoretical studies of religion from a wide range of disciplines and from all parts of the globe. This volume includes a special section on spirituality and hope that brings together theoreticists and practitioners who present original research on this important and neglected topic. Alongside this section are papers presenting studies on subjects such as civic participation, suffering with God, and spirituality. Together these papers represent important contributions that advance theory and evidence in a number of different fields of contemporary relevance to the study of religion.